TEMPORAL DYNAMICS OF PHYSICOCHEMICAL WATER QUALITY PARAMETERS IN AQUACULTURE POND - Bello, Mustapha M.; Abubakar , Lawan Aliyu (FUDMA Journal of Sciences, 2024)
In aquaculture production, water is held inside a fish pond for a certain period before discharging or recycling. During this period, the characteristics of the water vary due to the addition of fish feed and chemicals, as well as the fish metabolites. This study evaluated the temporal dynamics of the physicochemical water quality parameters in fish ponds. Grab samples were collected daily over 30 days, and physicochemical parameters such as pH, Electrical Conductivity (EC), Total Dissolved Solids (TDS), major cations and metals were evaluated. The concentrations of the cations fluctuated over the period, with the Ca having the highest variations. The highest concentration (19 mg/L) was observed on the 5th day whilst the lowest (12 mg/L) was observed on the 23rd day. The concentration of Mg fluctuated over the period, with an average of 4.35 mg/L. Overall, the concentrations of these cations in the pond water are in the following order: Ca > Mg > K, which indicates that the water is unlikely to pose any harmful effect on soil hydraulic conductivity. The concentrations of the metallic ions in the pond also varied over the period. However, the exit concentrations are below the recommended threshold values for irrigation. The SAR analysis showed an increasing trend over the period, with the value exceeding the FAO recommended threshold from the 14th day. This study has shown that most of the physicochemical parameters of the pond water fluctuate over time, but the effluent can still be used for irrigation.
Keywords: Aquaculture effluents; Sustainability; Irrigation water quality; Wastewater